PHYSOTHERAPY MANAGEMENT IN POST OPERATION SYRINGOMYELIA: A CASE STUDY - Salwa, S; Sudaryanto, Wahyu Tri; Wijaya, Katwa (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Syringomyelia is a disorder of the central nervous system, this disorder is often associated with the appearance of cysts (syrinx) in the spinal cord. The presence of this syrinx causes pressure on the spinal cord, thus it is followed by muscle weakness and pain. The incidence of syringomyelia cases is very little, namely 8.4/100,000 or only 2%. Physiotherapy treatment in cases of syringomyelia is usually in postoperative care. Due to the scarcity of this case, there is limited information regarding physiotherapy treatment in cases of syringomyelia.Case description: A 51-year-old woman was diagnosed with syringomyelia through an MRI scan, after undergoing surgery, she complained of silent pain. Following the surgery, the patient underwent rehabilitation by physiotherapy since she complained of silent pain on the upper limb.Intervention and Outcomes: The patient received treatment from physiotherapists in the form of IR and TENS. The intervention was given for 2 weeks, with a 10 minutes duration of IR and 15 minutes duration for TENS. Evaluation was done every week, where every week there was a reduction in pain, which was VDS (Verbal Descriptive Scale) 7/10 to 0/10.Discussion and Conclusion: Physiotherapy can handle the side effects that occurred after syringomyelia surgery 6 months ago, which in this study showed a decrease in the silent pain score. However, the decrease of silent pain is only temporary, because the patient continued to complain of discomfort the next day.